The feeling of familiarity (Acta Scientiarum. Human and Social Sciences, 2022)
The relationship between the phenomenology of imagination and the phenomenology of memory is an interestingly complicated one. On the one hand, there seem to be important similarities between the two, and there are even occasions in which we mistake an imagining for a memory or vice versa. On the other hand, there seem to be important differences between the two, and we can typically tell them apart. This paper explores various attempts to delineate a phenomenological marker differentiating imagination and memory, with a special focus on two proposed markers that have generated considerable philosophical discussion: the feeling of pastness and the feeling of familiarity. As we will find, neither of them proves to be up to the task at hand.  However, by way of a deeper exploration of the feeling of familiarity, we are able to tease out some important morals for efforts to differentiate imagination and memory on phenomenological grounds and, more generally, for efforts to engage in a descriptive phenomenological enterprise